THE EFFECT OF SELF-EFFICACY AND WORKLOAD ON EMPLOYEE PERFORMANCE THROUGH MEDIATING VARIABLES OF JOB SATISFACTION - Reza Farly Salampessy; R. Adjeng Mariana F (Jurnal Ilmu Pemerintahan Widya Praja, 2023)
The purpose of this study is to determine the impact of self-efficacy and workload on employee performance through the mediating variables of job satisfaction in regional financial and asset management institutions in West Java Province. The importance of knowing and analyzing employee performance is the fundamental reason for government activities and government goals in West Java Province to be achieved optimally. This study adopted a quantitative approach using primary and secondary data. The research data was collected using a questionnaire-form instrument, measured using Likert scale. The sample of this study included 122 government officials as respondents. The collected data is then analyzed gradually, starting from testing the validity and reliability of the question items on the research instrument, then testing classical assumptions so that the data can be used for the next stage. Additionally, the data were analyzed by conducting multiple regression to determine the direct impact of self-efficacy variables and workload on employee performance. The path analysis used in this study aimed to identify the indirect effects of self-efficacy variables and workload on employee performance through job satisfaction variables. The research results show that self-efficacy and workload have a significant impact on employee performance, with a determination value of 67.4%. Job satisfaction can have a positive and significant impact of 11.4%. The analysis results of the job satisfaction variable path can mediate the impact of self-efficacy and workload on employee performance. Key words: Self-Efficacy; Workload; Job Satisfaction and Performance.